Short-Term Impacts of COVID-19 Public Health Regulation on Consumer Food Purchases: A Case Study From a Grocery Store in Montana - Ebel, Roland; Byker-Shanks, Carmen (Frontiers in Sustainable Food Systems, 2022)
The mitigation measures (e.g., lockdown policies) in response to the COVID-19 pandemic impacted food systems in unprecedented ways, in both scope and immediacy. Food retail, for example, changed fundamentally in the United States, as access to nutritious food became limited, supply chain shortages were common, and mandatory public health measures led to behavior changes among customers and employees. In the present case study, we hypothesized that these changes led to food purchasing shifts of grocery store consumers. Such shifts are seen as an outcome of both endogenous factors at the individual level and exogenous factors at the government/policy level. Our case study sought to better understand how the pandemic and associated regulations shaped consumer food choices during the “hard” lockdown period in Montana during 2020. We selected 112 food products based on the highest sales in a Gallatin County, Montana, grocery store. They were analyzed by predefined food groups aligned to the Dietary Guidelines for Americans 2020. All purchases were processed for each selected food item during March and April 2019 (before the pandemic) and March and April 2020 (during the lockdown in Montana). To further describe the pandemic experiences qualitatively, we conducted semi-structured interviews with managers and employees from two stores in Gallatin County. Overall, we found that consumers increased purchases in most food groups during the pandemic, including nutrient-dense and energy-dense products, most outstandingly for starchy vegetables, legumes, and convenience food. Products with long shelf-life and that required preparation at home were preferred. Endogenous causes, specifically panic and rushing, were likely stronger drivers of consumer behavior and food choices than regulations. Nonetheless, lockdown policies impacted consumer food purchases. We present a series of policy and practice recommendations based on our findings and the emerging literature on this topic.